Keterampilan Penggunaan Platform E-learning Mahasiswa Kedokteran Hewan Universitas Nusa Cendana Melalui Pelatihan Daring di Masa Covid-19 - Dede Rival Novian (Indonesia Berdaya, 2022)
During the Covid-19 pandemic from March 2020 until now, students at the Faculty of Medicine and Veterinary Medicine, University of Nusa Cendana experienced difficulties in implementing an online learning system using the learning management system platform from the University of Nusa Cendana, especially first semester students who are using the online learning system for the first time. the Learning Management System platform from the University of Nusa Cendana. They have not fully mastered the various online learning features on the platform, such as logging in, filling out the attendance list, downloading materials, conducting discussions and submitting assignments. The purpose of this service is to improve students' knowledge and skills in using the Nusa Cendana University learning management system platform. The subjects of this service are first semester students at the Faculty of Medicine and Veterinary Medicine, University of Nusa Cendana. The training was carried out using several methods, such as lectures, questions and answers, and direct practice using the learning management system platform. Data were collected by using the observation method. The results of the training showed that all students managed to have the ability to use the University of Nusa Cendana Learning Management System platform, they had the ability to login into the system, fill out attendance lists, download learning materials, and conduct discussions and collect assignments. After this, they will be able to conduct bold learning training that is more organized and more open in using the learning management system of the University of Nusa Cendana platform.  Abstrak: Selama masa pandemic Covid-19 dari bulan Maret 2020 sampai sekarang, mahasiswa di Fakultas Kedokteran dan Kedokteran Hewan Universitas Nusa Cendana mengalami kesulitan dalam menerapkan sistem pembelajaran dalam jaringan menggunakan platform learning management sistem dari Universitas Nusa Cendana, terutama mahasiswa semester satu yang baru pertama kali menggunakan platform Learning Management System dari Universitas Nusa Cendana tersebut. Mereka belum sepenuhnya menguasai berbagai fitur pembelajaran online di platform tersebut, seperti login, mengisi daftar hadir, mengunduh materi, melakukan diskusi dan mengumpulkan tugas. Tujuan dari pengabdian ini adalah untuk meningkatkan pengetahuan dan keterampilan mahasiswa dalam menggunakan platform learning management system Universitas Nusa Cendana. Subyek pengabdian ini adalah mahasiswa semester satu di Fakultas Kedokteran dan Kedokteran Hewan Universitas Nusa Cendana. Pelatihan dilaksanakan dengan beberapa metode, seperti ceramah, tanya jawab, dan langsung praktek langsung menggunakan platform learning managemen system. Pengumpulan data dilakukan dengan metode observasi. Hasil pelatihan menunjukkan bahwa semua mahasiswa berhasil memiliki kemampuan dalam menggunakan platform Learning Management System Universitas Nusa Cendana, mereka memiliki kemampuan dalam melakukan login ke sistem, mengisi daftar hadir, mengunduh materi pembelajaran, melakukan diskusi dan mengumpulkan tugas. Setelah pelatihan ini, mereka akan dapat melakukan pembelajran daring yang lebih terorganisir dan lebih termotivasi dalam menggunakan platform learning management system Universitas Nusa Cendana.